2022
DOI: 10.3389/fmicb.2021.796363
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolic Pathways Analysis and Subtractive Genomics Profiling to Prioritize Potential Drug Targets Against Streptococcus pneumoniae

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
0
12
0
2
Order By: Relevance
“…It has been reported that cytoplasmic proteins are an excellent therapeutic target and may be readily targeted with drugs [ 29 ]. Additionally, ~70 percent of FDA-approved medications are claimed to target enzymatic proteins because of their substantial participation in numerous pathways.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that cytoplasmic proteins are an excellent therapeutic target and may be readily targeted with drugs [ 29 ]. Additionally, ~70 percent of FDA-approved medications are claimed to target enzymatic proteins because of their substantial participation in numerous pathways.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that cytoplasmic proteins are an excellent therapeutic target and may be readily targeted with drugs [ 56 ]. Additionally, ~70 percent FDA approved medications are claimed to target enzymatic proteins because of their substantial participation in numerous pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins participating in unique pathways may exhibit homology with human and host citrus plant [52].…”
Section: Discussionmentioning
confidence: 99%